High-temperature corrosion behaviour of stainless steel welds in molten NaNO3-KNO3-KCl environment for concentrated solar power - Joy, Tony; Mori, Stefano; Sumner, Joy (Elsevier, 2025)
The use of fossil fuels has caused adverse effects, notably carbon emissions and climatic change. Thermal energy storage (TES) systems can be used to store energy and, when integrated with CSP, can help mitigate the intermittency of renewable sources. Higher TES working temperatures correspond to higher efficiencies which may lower costs. Various substances have been proposed as TES media; molten salts (MS) emerge as one of the most attractive options due to their stability at high temperatures. However, they can accelerate corrosion on materials, and therefore, compatibility between materials and media is crucial. Additionally, the impact of MS on welds (or welded components) has received less attention than for parent material. To address this research gap, this study compares the corrosion behaviour of plain and welded SS316L and SS304L in a mixture of 10NaNO3-78KNO3-12KCl mol% at 600 °C for up to 500 h. The samples were analysed by dimensional metrology (DM), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). Dimensional metrology shows a higher metal loss and sound metal loss for SS304L than SS316L. SEM micrographs showed the formation of non-adherent corrosion products on alloys surfaces. The EDS shows a selective dissolution of Fe and Cr, along with Na, K and Cl penetration into the alloy. Comparing the results, the welded areas experienced higher metal loss as compared to plain alloy samples. Another key observation was that the SS304L samples displayed lower overall corrosion resistance than SS316L.
Keywords: 40 Engineering; 7 Affordable and Clean Energy; 13 Climate Action; Molten chloride; High temperature corrosion; Stainless steels; Dimensional metrology; Thermal energy storage; Scanning electron microscopy